Properties of glycerol-plasticized alginate films obtained by thermo-mechanical mixing. (February 2017) - Gao, Chengcheng; Pollet, Eric; Avérous, Luc
Abstract: Different plasticized alginates have been prepared by thermo-mechanical mixing for the first time. In this study, sodium alginate of high molar mass has been processed with glycerol as a nonvolatile plasticizer and water as a de-structuring agent. The obtained materials have been characterized and compared to similar plasticized polysaccharide systems based on starch and chitosan from previous studies. After equilibration, the final water content of glycerol-plasticized alginate stays quite high with values slightly above those of the equivalent starch- or chitosan-based plasticized materials under the same conditions. This can be explained by the more hydrophilic character of plasticized alginate. The effect of the glycerol content on the microstructure and properties of alginate-based materials was examined. X-ray diffraction results showed that neat alginate granules were largely destructured, and that glycerol increased the mobility of alginate chains while promoting the crystallization of the alginate chains with structural reorganization. The addition of glycerol resulted in a decrease in tensile strength and Young's modulus and an increase in elongation at break. However, elongation at break decreased when glycerol content exceeded 30 wt% due to a major segregation phenomenon. Compared to thermoplastic starch with the same glycerol content obtained by thermo-mechanical mixing, plasticized alginate was found to be stiffer. The thermal decomposition temperature of alginate decreased with the incorporation of glycerol. Finally, transparent, soft, and easy-to-handle manually films were obtained using a multistep process that has been previously developed for starch and chitosan to obtain thermoplastic polysaccharides, with easy scale-up to obtain large-scale production. Graphical abstract: Highlights: Plasticized alginates prepared by thermo-mechanical mixing for the first time. Transparent, soft, and easy-to-handle manually films were obtained. Glycerol is a good plasticizer to elaborate alginate materials by thermo-mixing. Glycerol gives high alginate destructuration and high mechanical properties. Plasticized alginates behaviors compared with chitosan or starch-based materials.